Fisheries resources status of Selabung River during pre construction of Komering 2 Dam, Tigadihadji, South Sumatra. Issue 1 (July 2020) - Marini, M; Husnah,; Vipen,; Purwoko, R M; Prianto, E
Abstract: In the period of 2015-2019, 45 dam will be constructed in Indonesia. One of them is a cascade Komering 2 dam constructed in Selabung river, a tributary of Komering river, located in Tiga Dihadji District, South Sumatra. The present Perjaya irrigation dam which was built in 1991 in the down stream of Komering 2 reservoir experienced sedimentation and habitat loss of floodplain fisheries resource. Construction of Komering 2 dam could give negative effects to aquatic and fisheries resource of Selabung and Komering river. The information on the present state of fisheries resources in Selabung prior to the dam construction is important so that the impact of dam construction could be determined. A study in order to get information on the current state of fisheries resource in Komering 2 dam was conducted at three sampling sites in February and September 2018. Parameters observed were habitat characteristics and fish resources. The data was collected through field sampling and structured interview with the fishermen. Results of this study revealed that at the up stream, the riparian area is undisturbed covered by dense conservation forest while at the down stream inhabited by 300 families and 10 % of them are fishermen. Riparian area was covered by agriculture comodity. River bed was covered by peeble stone with most of water quality parameters still fulfil water quality standard of Indonesian regulation. Twenty three (23) fish species were recorded and six of them were dominant. Degradation of fish resources is noticed indicated by loss of 4 fish species, decreasing catch of 5 fish species, two introduced fish species and decreasing individual size of economical fish such as mahseer.